Evaluation of Composite Structures by Light Microscopy and Image Analysis - Markovicova, Lenka; Hurtalova, Lenka; Zatkalikova, Viera; Garbacz, Tomasz (Manufacturing Technology Journal, 2014)
A composite is a material which is made up of two or more distinct materials. Composite materials are generally used for buildings, bridges and structures such as boat hulls, swimming pool panels, race car bodies, shower stalls, bathtubs, storage tanks, imitation granite and cultured marble sinks and counter tops. As a result of absorption of liquids usually occurs a change in volume, which is referred to as swelling. This process can give rise to physical and chemical properties of polymers.NIS - Elements 3.0 was used to evaluate the microstructure of composite materials with different contents of ferrite powder filler. Using NIS - Elements 3.0 assessed the number of particles Sr ferrite surface area and perimeter Sr ferrite particles and the volume fraction of Sr ferrite in the microstructure.
Keywords: composite; polyethylene; image analysis; chemical resistance; powder filler